Analisis Chi Square Untuk Mengetahui Hubungan Antara Karakteristik Konsumen Dengan Sikap Konsumen - Fathorrozi Ariyanto; Tony Yulianto; Jamilatul Isti’adah (Mathematics Department, Faculty of Sciences and Technology Unisda Lamongan, 2025)
Aprilia Handmade is a unique brand, handicraft, creative and others. Consumer priorities towards products are influenced by their attitudes that influence purchases and tight competition. This study aims to determine whether there is a relationship between consumer characteristics and consumer attitudes towards fashion products (Case study at Aprilia Handmade Sumenep). Data collected using questionnaires, observations, and documentation, with the population being consumers who have visited or buyers at Aprilia Handmade Sumenep, where the sampling technique was carried out with a purposive sampling method with a sample size of 100 respondents. The data analysis method uses Contingency Coefficient Analysis to relate the relationship between products, promotions, prices, and purchasing decisions. From the analysis, it was obtained that the quantitative results using Chi Square X2 analysis were: Products with a value of X2 = 415, Promotions with a value of X2 = 4.589, Prices with a value of X2 = 0.671, and Purchase decisions with a value of X2 = 1.523. From manual calculations, the same results were obtained using SPSS window 20.0. The results of the study indicate that between products, promotions, prices, and purchasing decisions have a significant relationship with consumer attitudes towards fashion products. This is indicated by the results of the interpretation of the contingency coefficient which is quite strong or quite good.